Nature and sense of social capital in the revival of the cooperative movement - Сікора, Олена Анатоліївна; Сидорчук, Ористлава Григорівна (Technology audit and production reserves, 2015)
The role of social capital in activity of networks of civil activity is analyzed. The main approaches to understanding the concept of cooperation and the role of the cooperative sector in social and political, economic life of the citizen are outlined. It is investigated that cooperation has great potential for social support of the general population, especially of vulnerable social; focused on human values and is a source of social capital. It is determined that the neglect of social capital in creation of cooperatives is a major problem of reducing the cooperative movement in Ukraine. The main reasons for decline of the cooperative movement are the lack of understanding of its content and substance, prevalence of vertical connection and identification with the cooperation of the socialist period. Directions of the state activity to promote the revival of the cooperative movement are proposed. There are providing the legal support by creating a legal framework which would be assigned the status of cooperatives and cooperative systems, principles of construction and operation, guarantees to protect cooperatives, etc.; providing conditions for financial stability of cooperatives.